Synergistic Influence of Gum Arabic and Iodide Ion on the Corrosion Inhibition of Aluminium in Alkaline Medium - Umoren,S. A. (2009)
The effect of iodide ion on the corrosion inhibition of aluminium in NaOH in the presence of Gum Arabic (GA) was studied using weight loss and hydrogen evolution techniques at 303 and 313 K. The results obtained showed that inhibition efficiency increased with increasing GA concentration. The inhibiting action of GA was considerably enhanced by the addition of KI. The adsorption of KI, GA alone and in combination with iodide ion was found to obey Temkin adsorption isotherm. The inhibiting effect of GA and (GA+KI) increased with increase in temperature of the corrosion medium, indicating chemical adsorption mechanism. Synergism parameter evaluated was found to be greater than unity for the different concentrations of GA, which shows that the enhanced inhibition of GA caused by the addition of iodide ion is due to synergistic effect. It could be deduced from the thermodynamic parameters obtained that adsorption of GA alone and in combination with KI onto the metal surface is spontaneous.